Effect of Using Local Natural Fibers and Synthetic Fibers on the Properties of High Strength Self-Compacted Concrete - Muhammad S. Sawarkih, Hassan M. Hassan, Mohammed A. Arab (International Journal of Advanced Science and Technology, 2020)
The world’s concern about global warming increased every day and reflected on the ‎concrete industry. Egypt, as one of the developing countries, has huge renewable resources of ‎natural and vegetable materials. Natural fibers have received attention from many researchers as one of the ‎eco-friendly and sustainable building materials. Four types of natural fibers from the Sinai ‎Peninsula in Egypt are studied as a concrete constituent material. The effect of used fibers on the ‎properties of High Strength Self Compacted Concrete (HSSCC) was investigated. The Palm, ‎Thymelaea, Alhagi Graecorum, and Aloe-Vera were used as natural fibers while glass and ‎polypropylene were used as synthetic fibers. Fresh and hardened concrete properties and durability using sorptivity test were investigated. All fibers improved durability, compressive, ‎indirect tensile and flexural strengths of HSSCC where Alhagi Graecorum fibers were the best ‎among the four natural types while glass fibers were the best among all types. Thirteen reinforced ‎HSSCC beams containing the optimum content for different types and lengths of the used fibers ‎were cast to investigate the load-deflection behavior and toughness of HSSCC beams. Results revealed that all the used natural fibers especially the three new types give acceptable results and could be used successfully in the concrete industry.‎